2018
DOI: 10.1186/s12934-018-0919-6
|View full text |Cite
|
Sign up to set email alerts
|

Substrate sustained release-based high efficacy biosynthesis of GABA by Lactobacillus brevis NCL912

Abstract: BackgroundGamma-aminobutyric acid (GABA) plays a significant role in the food and drug industries. Our previous study established an efficient fed-batch fermentation process for Lactobacillus brevis NCL912 production of GABA from monosodium l-glutamate; however, monosodium l-glutamate may not be an ideal substrate, as it can result in the rapid increase of pH due to decarboxylation. Thus, in this study, l-glutamic acid was proposed as a substrate. To evaluate its potential, key components of the fermentation m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
46
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(50 citation statements)
references
References 40 publications
(61 reference statements)
4
46
0
Order By: Relevance
“…Different strains of Lb. brevis produce GABA in the range from 15.0 mg/L to 205 g/L [17,18]. Similarly, different Lb.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Different strains of Lb. brevis produce GABA in the range from 15.0 mg/L to 205 g/L [17,18]. Similarly, different Lb.…”
Section: Introductionmentioning
confidence: 98%
“…Up to now, the highest yield of GABA by Lb. brevis is 205 g/L [18]. At the same time, various strains of one species have obvious differences in GABA productivity ( Supplementary Table S2).…”
Section: Introductionmentioning
confidence: 99%
“…As mentioned above, a number of LAB carry two GAD-encoding genes, gadA and gadB. Frequently, studies have focused on the purification and characterization of GadB, e.g., from E. raffinosus [75], L. plantarum [79], L. brevis [78], L. sakei [80], L. paracasei [18] since the expression levels of recombinant GadB are typically higher than those for GadA [55]. A recent study by Wu et al showed that gadA transcript was highly upregulated (55-fold) in strain L. brevis NPS-QW-145 at the stationary phase of growth.…”
Section: Biochemical Insights Into Glutamate Decarboxylase From Lactimentioning
confidence: 99%
“…Good amounts were obtained by growing Lactobacillus buchneri in corncob hydrolysate and xylose [ 14 ] or Lactobacillus rhamnosus in fermented adzuki bean milk [ 15 ]. Lactobacillus brevis strains isolated from quinoa sourdough [ 16 ] or kimchi [ 17 ] fermentation as well as L. brevis cultures fortified with divalent cations (Mg 2+ ) and tween-80 [ 18 ] also display promising GABA yields. Co-cultures of Corynebacterium glutamicum and Lactobacillus plantarum [ 18 ], as well as entrapped [ 19 ] or immobilized [ 20 ] L. brevis cells were also described together with immobilized GAD enzyme [ 21 ] as a means to obtain economically sustainable GABA production.…”
Section: Introductionmentioning
confidence: 99%